Diagnosis and treatment of deep neck abscess due to congenital piriform sinus fistula in children - Bi,Jing (2021)
Abstract Introduction: Congenital piriform sinus fistula is a relatively rare type of disease in clinical practice, most occurring during childhood, but doctors have insufficient knowledge regarding this disease, easily misdiagnosing it. Objectives: This study aimed to identify the characteristics of deep neck abscess due to congenital piriform sinus fistula in children. Methods: We performed a retrospective study of 21 cases from January 2016 to August 2018 in our hospital. The onset age, clinical characteristics, auxiliary examination and clinical treatment of the patients was summarized to analyze the diagnosis, treatment characteristics and prognosis. Results: Children from 11 days to 12 years-old were enrolled, with an average age of 3.5 years. Twenty patients had left congenital piriform sinus fistula and 1 had right congenital piriform sinus fistula. Cervical enhanced computed tomography imaging showed gas-liquid equilibrium or air-shadow in the abscesses in 18 cases, and neck ultrasound demonstrated gas echo in the thyroid region in 10 cases. All patients underwent low temperature plasma to seal the internal fistula and returned to the hospital for electronic laryngoscope and neck ultrasound examination at 3 months, 6 months and 1 year after the surgery. No recurrence occurred in any patient. Conclusion: Congenital piriform sinus fistula is an important cause of deep neck abscess in children. The presence of purulent gas-liquid equilibrium or air shadow in cervical-enhanced computed tomography or ultrasound suggests a high possibility of the presence of an internal fistula, and endoscopic low temperature ablation can be done at the same time as the diagnostic endoscopy.